Recurrent orbital space-occupying lesions: a clinicopathologic study of 253 cases - Tang, Weiqiang; Hei, Yan; Xiao, Lihua (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
Objective: To analyze the clinical features, histopathologic classification and frequencies of various types of recurrent orbital space-occupying lesions. Methods: A retrospective study was carried out in 253 consecutive patients with recurrent orbital space-occupying lesions treated by surgical excision in the Institute of Orbital Diseases, the General Hospital of the Armed Police Force from January 2009 to December 2010. Results: The patients included 123 males and 130 females aged 2 to 78 years (mean, 36.2 years), and the last recurrence interval after operation ranged from 1 month to 40 years (median, 4.75 years). Of all the cases, 159 (62.8%), 65 (25.7%), 20 (7.9%), 8 (3.2%) and 1 (0.4%) had previously experienced once, twice, three, four and six times of surgeries, respectively. Among them, 29 (11.5%) cases had recurred 3 times or over, and 37 (14.6%) cases got recurrence in 10 or more years postoperatively. Most of the patients with local recurrence presented with various clinical manifestations, while 31 (12.3%) cases were symptom-free. Two hundred and thirty-one (91.3%) cases underwent surgical removal of the recurrent orbital lesions, and another 22 (8.7%) cases had to receive the exenteration of orbit. Categories of these recurrent orbital lesions after operation were as follows: lacrimal gland tumors, 65 (25.7%) cases; vasogenic diseases, 54 (21.3%) cases; neurogenic tumors, 42 (16.6%) cases; secondary tumors, 24 (9.5%) cases; orbital inflammation, 21 (8.3%) cases; myogenic tumors, 14 (5.5%) cases; fibrous and adipose tumors, 12 (4.7%) cases; lympho-hematopoietic tumors, 7 (2.8%) cases; bone or cartilage tumors, 7 (2.8%) cases; orbital cysts, 6 (2.4%) cases; and indefinitely differentiated tumor, 1 (0.4%) case. The 10 top histopathologic diagnoses were lacrimal gland pleomorphic adenoma, hemangiolymphangioma, lacrimal gland adenoid cystic carcinoma, meningioma, inflammatory pseudotumor, neurofibroma, sebaceous gland carcinoma, vascular malformation, rhabdomyosarcoma and hemangioma. Conclusions: The variety of recurrent orbital lesions after operation includes mainly of tumors except for vascular malformation and orbital inflammatory lesions. The lacrimal gland epithelial tumor is most prone to relapse after resection, and early and longer-term postoperative follow-up is needed.